Evaluation of Resources of a Part Depending on its Renewal Density - Masienko Ivan (EDP Sciences, 2021)
The article proposes a method to obtain the numerical characteristics of the assessment of the resource of a part on the basis of experimental data on the element renewal density, which can significantly reduce the cost of labor, funds and time to obtain the required results. A methodological approach to the use of experimental data on the renewal density to evaluate the numerical characteristics of the original law of distribution of the resource of an element is presented.